Bilateral Herpetic Keratitis After Bilateral Intravitreal Bevacizumab for Exudative Macular Degeneration. Issue 7 (July 2017) - Derham, Angeline M.; Chen, Eric; Bunya, Vatinee Y.; O'Malley, Ronan E.
Abstract : Purpose: To report a case of bilateral herpetic epithelial keratitis after bilateral intravitreal bevacizumab injections for the treatment of exudative age-related macular degeneration. Methods: A 66-year-old man with diabetes and an extensive history of bilateral anti-vascular endothelial growth factor treatments for exudative age-related macular degeneration received an intravitreal bevacizumab injection in the right eye and triple therapy (bevacizumab, photodynamic therapy, and triamcinolone acetonide) in the left eye. After 4 days, he presented with pain, photophobia, tearing, and decreased vision in both eyes. Slit-lamp examination revealed bilateral dendritic epithelial lesions with terminal bulbs, and he was diagnosed with bilateral herpes simplex epithelial keratitis. Results: The patient was treated with ganciclovir ophthalmic ointment and oral acyclovir with resolution of signs and symptoms. Conclusions: To our knowledge, this is the first documented account of bilateral herpetic epithelial keratitis after bilateral intravitreal bevacizumab injections.